Methods of educating the younger generation in the spirit of respect for elders (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines the socio-pedagogical mechanisms through which the Kyrgyz tradition of respecting elders has been preserved and transmitted from generation to generation. Based on empirical data and theoretical analysis, the study demonstrates that the sustainability of this moral norm is closely linked to the effective traditional methods and means of upbringing used in family and community practices. Drawing on the works of G.N. Volkov, A.E. Izmailov, A. Alimbekov, and R. Umarova, the research systematizes the folk pedagogical methods that shape children’s moral consciousness, behavioral habits, and value orientations. The study identifies key groups of methods—including consciousness-forming, behavior-shaping, and behavior-stimulating practices—and provides detailed descriptions of storytelling, advising, explanation, example-setting, blessing, discouragement, and other culturally embedded techniques. The findings confirm that folk pedagogy remains a powerful mechanism for moral education, where emotionally rich, situationally appropriate, and socially monitored practices ensure children’s acquisition of respectful behavior toward elders.
Keywords: Folk pedagogy; respect for elders; Kyrgyz traditional culture; moral upbringing; pedagogical methods; socialization; value formation; behavioral norms; ethno-pedagogy